The Influence of Live Streaming, Brand Awareness, and Brand Image on Purchase Interest in Shopee E-Commerce among Students of Universitas Muhammadiyah Surakarta - Purwaningrum, Revi Oktaviani; Saputro, Edy Purwo (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research provides a comprehensive understanding of the factors that influence Universitas Muhammadiyah Surakarta students' purchase intentions towards Shopee, an online store. A study showed that live streaming did not have a significant impact on purchase intent on the platform. However, it is important to highlight that the impact of brand awareness and brand image on sales is both positive and substantial, emphasizing their significance in marketing strategies. This shows that compared to the Live Streaming factor, brand awareness and image have a more dominant influence on purchasing decisions. These positive results show that efforts to increase awareness and develop strong brand awareness can be an effective strategy in increasing purchasing interest in the Shopee e-commerce community among Muhammadiyah University Surakarta students. Therefore, the scholars who have studied it.